Defining a serum cortisol cutoff level post-CRH stimulation for diagnosing ACTH deficiency: A retrospective study validated by a nationwide registry - Izuchi, Tetsushi; Iwama, Shintaro; Yamagami, Ayana; Kobayashi, Tomoko; Suzuki, Koji; Murase, Takanori; Ando, Masahiko; Murasawa, Shingo; Mukai, Kosuke; Takagi, Hiroshi; Fukuoka, Hidenori; Handa, Tomoko; et al. (Frontiers in Endocrinology, 2026)
BackgroundThe corticotropin-releasing hormone (CRH) stimulation test is used to diagnose adrenocorticotropic hormone (ACTH) deficiency; however, the serum cortisol cutoff value indicating impaired response on this test (18 µg/dL [approximately 500 nmol/L]) was established from the insulin tolerance test. We aimed to define a serum cortisol cutoff after CRH stimulation to diagnose ACTH deficiency.MethodsPatients who underwent CRH stimulation at Nagoya University Hospital from 2016 to 2022 were divided retrospectively into two groups based on the need for hydrocortisone replacement at final follow-up (discovery cohort). Plasma ACTH and serum cortisol levels were measured at baseline and 30, 60, 90, and 120 minutes post-CRH administration using a current monoclonal antibody-based cortisol assay. The optimal cortisol cutoffs at each time point were determined by receiver operating characteristic (ROC) analysis. These cutoffs were validated using a nationwide disease registry in Japan (validation cohort).ResultsIn the discovery cohort (n = 227), cortisol levels were significantly higher in patients who did not receive hydrocortisone therapy (n = 136) than in those who did (n = 91) at all time points (p < 0.001). ROC analysis revealed that a 30-minute post-CRH cortisol level of 12.6 µg/dL (347.6 nmol/L) provided the best diagnostic performance to identify patients not requiring hydrocortisone therapy (sensitivity: 88.2%; specificity: 92.3%; AUC: 0.969). In the validation cohort (n = 52), this cutoff was confirmed as optimal (sensitivity: 81.0%; specificity: 86.4%; accuracy: 83.7%).ConclusionA 30-minute post-CRH serum cortisol level of 12.6 µg/dL is a useful cutoff for diagnosing ACTH deficiency.